Skyscraper One World Trade Center in New York City – the modern green office building with a hybrid structure - Golasz-Szołomicka, Hanna; Szołomicki, Jerzy (Budownictwo i Architektura / Civil and Architectural Engineering, 2018)
This article presents elements of architectural and structural analysis of the safest and most environmentally-friendly skyscraper of One World Trade Center, which is the new symbol of New York located in Lower Manhattan. This building apart from the obvious symbolic dimension of the future and hope is a showcase of the most advanced technology. Because of this, the 1WTC design exceeds New York’s building standards and sets new standards for new high-rise buildings. This skyscraper is an octahedron based on a rectangular base, resembling a natural crystal. As the height increases, its edges are chamfered, signifi cantly reducing the impact of the wind, which is a major determinant in the design of high-rise buildings in New York. The article presents design solutions from the point of view of innovative architecture, construction, urban design, security and sustainable building. The design team used state-of-the-art methods to maximize the effi ciency of the building, minimize waste and pollution, save water, improve air quality and reduce the impact of other buildings. One World Trade Center received the LEED Gold Certifi cate as an Energy-Effi cient Building.